PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS LEARNING CYCLE 5E UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Ester Willu Kaka; Hunaepi Hunaepi; Masiah Masiah (Bioscientist : Jurnal Ilmiah Biologi, 2016)
ABSTRACT:Theaimsofthisresearchistodeveloping studentworksheetofintegratednatureofscience based of5elearning cycle modelto improvestudentconceptualunderstanding. TheMastery of the conceptcanbedefinedas theability ofstudentsto understandthemeaning ofscientific,that is understanding ofconcepttheoretically anditsapplication ineveryday life. This researchcountedin reseaechand development (R&D),andthemodel referenced indeveloping thisstudentworksheetof integrated natureof science isADDIEModel (Analysis, Design,Development,Implementation, Evaluation).Thedevelopmentofthisstudentworksheetofintegratednatureofscienceisonlyuntil thestageofdevelopmentalone.Aspectsofstudentworksheetofintegratednatureodsciencethat is developedinthisresearch includeaspectsoffeasibility,practicality,andeffectiveness.Basedonthe results of the research to test the feasibility, practicality, effectivenessand students'response to student worksheetof integratednatureofscience, canbeconcluded: the validity of the developmentisdone to determinethefeasibility ofstudentworksheetofintegratednatureofsciencebasedlearning cycle5e refers to the resultsof theassessmentitcanbeconcluded thatstudentworksheethavevery decent categorywithapercentageoftheaverageoflecturejudgmentis76.78%,andpercentagefrom thethe teacher judgmentis79,31%.Practicality ofstudent workheetwereassessedby two(2)teacherof integratednatureofscience,thatstudentworksheetisverypracticalcategorywith94,8%.Theresults oftrialson theeffectivenessofstudentworksheets totaling 34students, thatthe studentworksheetis categorizedquiteeffectively withapercentageof79.55%andtheresultsoftheanalysisteststudents' responsesarerepresentedby10students,LKScategorizedasveryfeasiblewithapercentageof 76.66%, thus thedevelopedstudentworksheetbased learning cycle5efeasibletobeusedto improve studentconceptualunderstanding.